Analisis Persepsi Terhadap Tampilan Budaya Korea pada Iklan E-Commerce Shopee di “Tanggal Cantik” 12.12 1.1 Dan 2.2 - Ririn Puspita Tutiasri; Maulidya Rahmatika Aulia; Arfianti Valerina Alfi; Nabila Dafa Purwa (Universitas Islam Balitar, 2021)
This research aims to determine how teenager’s perceive Korean cultural appearance presented by Korean Idol Stray Kids on Shopee's E-commerce advertisement on 12.12 1.1 and 2.2. This research uses a qualitative method, where the researcher tries to provide an overview of a group or phenomenon that are happening in society. Collecting data in this study using interview / interview techniques. Researchers try to get research data in the field. The results of this research show how teenager’s perceptions of Korean Cultural Appearance presented by Korean Idol Stray Kids on Shopee's E-commerce advertisement on 12.12 1.1 and 2.2. The results of teenager’s perceptions are various and measured from different points of view. The appearance of Korean culture presented by Korean Idol Stray Kids in Shopee's E-commerce advertisement on 12.12 1.1 and 2.2 was less influential for a group of teenager’s because some informants said that discount were more interesting than the Brand Ambassador used by Shopee.